Influence of H+ ion on microstructure and electrochemical behavior passive film formed on stainless steel-304 in low concentrated sulfuric acids - Natarajan, R (Recent Research in Science and Technology, 2016)
The investigation focused toward microstructure and electrochemical changes caused by proton on a passive film formed on the surface of stainless steel-304 in lower concentrated sulfuric acid solutions (exclusively 0.5, 1.0, 2.0, and 5.0 N concentrations). Dissociation rate of the proton in the acid was reduced due to increasing of acid concentration from 0.5 to 5.0 N, which causes anodic shift at open circuit potential region and cathodic shift in different passivation potential regions. Proton enhances different electrochemical behaviors such as activation, primary, secondary passive, and transpassive behaviors, which was concluded by increasing of current value in these regions. AC impedance parameters such as double layer capacitance (Cdl ), charge transfer resistance (Rct ) are compared with selective polarization parameters. Microstructure and chemical entities present in the passive film were examined through scanning electron microscopy and X-ray photoelectron spectroscopic techniques. The role of H+ and SO42- ion on metal dissolution and passive film formation have been discussed.